Developing a Novel Gene-Delivery Vector System Using the Recombinant Fusion Protein of Pseudomonas Exotoxin A and Hyperthermophilic Archaeal Histone HPhA - Deng, Xin; Zhang, Guoli; Zhang, Ling; Feng, Yan; Li, Zehong; Wu, GuangMou; Yue, Yuhuan; Li, Gensong; Cao, Yu; Zhu, Ping (PloS one, 2015)
Non-viral gene delivery system with many advantages has a great potential for the future of gene therapy. One inherent obstacle of such approach is the uptake by endocytosis into vesicular compartments. Receptor-mediated gene delivery method holds promise to overcome this obstacle. In this study, we developed a receptor-mediated gene delivery system based on a combination of the Pseudomonas exotoxin A (PE), which has a receptor binding and membrane translocation domain, and the hyperthermophilic archaeal histone (HPhA), which has the DNA binding ability. First, we constructed and expressed the rPE-HPhA fusion protein. We then examined the cytotoxicity and the DNA binding ability of rPE-HPhA. We further assessed the efficiency of transfection of the pEGF-C1 plasmid DNA to CHO cells by the rPE-HPhA system, in comparison to the cationic liposome method. The results showed that the transfection efficiency of rPE-HPhA was higher than that of cationic liposomes. In addition, the rPE-HPhA gene delivery system is non-specific to DNA sequence, topology or targeted cell type. Thus, the rPE-HPhA system can be used for delivering genes of interest into mammalian cells and has great potential to be applied for gene therapy.